Estado e comunicação : uma análise das TVs Legislativas estaduais no Brasil - Melo, Paulo Victor Purificação (2014)
The purpose of this presente essay is to investigate the segment of State´s Legislative Televisions in Brazil, establishing as specific object of study the analysis of the technology offered to acess the schedule, models of management and the schedule profile of these broadcast TVs. The research focuses on the structure and organization of the TVs, extending them as a part of a complex public communication system which had its historic development imprinted by a minor complementary condition facing the brazilian State´s attempt to privilege the private initiative´s exploitation of the broadcasting service. The Legislative TVs in Brazil were created less than 20 years ago and have been one of the most important instruments used by the parliament in approximation and dialogue with society. It, furthermore, represents an improvement of the perspective of communication democracy´s systems, especially because it has distinct content in comparison to comercial media. The State´s Legislative TVs, specially mentioning the models of management, are also configured as space property of the Legislative Assembly Directors Table, where the guarantee of social participation determinant for the accountability and its conditions as vehicle of public communication is revealed as a necessary challenge. This aspect is intensified by the absence of a legislature to establish conditions for functionality, management and use of these TVs, either federal, state or municipal, becoming even more difficult to be supervised and controlled by society.